Conflict Management Strategies in Multicultural Education Subjects for Class V Students MI Muhammadiyah 02 Mariyai - Hartinah, Hartinah; Fauziah Badarab, Inda; Nur Hasanah, Ida; Madjid, Ilham (Journal of Quality Assurance in Islamic Education (JQAIE), 2023)
Introducing multicultural education early to familiarize students with social and cultural diversity is essential. Schools have a significant role in teaching and organizing multicultural education to form students with high social spirit and tolerance in viewing diversity and differences. However, in practice, some conflicts occur in multicultural education carried out by schools. So, it demands that schools have strategies to overcome these conflicts. This study aims to know and examine more deeply how management strategies become solutions to resolve multicultural disputes in schools. This type of research is descriptive qualitative. The data in the study were obtained from observations made by researchers at the location, the results of direct interviews conducted between researchers and informants related to the problems studied, and archival documentation related to the issues explored. Based on the data that has been obtained, the results of the study are known that one of the conflict management strategies in schools in multicultural education is to approach students and find out the causes of conflicts/problems, assist students in resolving multicultural conflicts that occur communicating or providing explanations and understanding related to multicultural education, and integrating multicultural education into subjects.